Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Step-by-step explanation:
Use the Factor Theorem,
" if x-a is a factor of f(x), then f(a) =0,
So here, since x-3 is a factor then f(3)=0,
So first step, plug in 3 for x for the serperate equations.
[tex] {3}^{2} + ( p + q)3 - q = 0[/tex]
[tex]2(3) {}^{2} + (p - 1)3 + (p + 2q) = 0[/tex]
Simplify both equations,
[tex]9 + 3p + 2q = 0[/tex]
[tex]15 + 4 p + 2q = 0[/tex]
Isolate the constants,
[tex]3p + 2q = - 9[/tex]
[tex]4p + 2q = - 15[/tex]
We have a system of equations so let eliminate a variable, by subtracting the two equations.
[tex] - p = 6[/tex]
[tex]p = - 6[/tex]
Plug p back in for any one of the equations to find q.
[tex]3( - 6) + 2q = - 9[/tex]
[tex] - 18 + 2q = - 9[/tex]
[tex]2q = 4.5[/tex]
So p is -6
q is 4.5
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.